2015
DOI: 10.1371/journal.pone.0121053
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Plant Risk Evaluation (PRE) Tool for Assessing the Invasive Potential of Ornamental Plants

Abstract: Weed Risk Assessment (WRA) methods for evaluating invasiveness in plants have evolved rapidly in the last two decades. Many WRA tools exist, but none were specifically designed to screen ornamental plants prior to being released into the environment. To be accepted as a tool to evaluate ornamental plants for the nursery industry, it is critical that a WRA tool accurately predicts non-invasiveness without falsely categorizing them as invasive. We developed a new Plant Risk Evaluation (PRE) tool for ornamental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…When evaluating the predictive power of the 56 questions of the final PRE tool, Conser et al (2015) detected that only 11 of them showed statistical significance in separating invasive from non-invasive species. Four were the result of merging two similar questions, where both were significant or near significant (e.g., different methods of vegetative reproduction, various biotic and abiotic propagule dispersal mechanisms).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When evaluating the predictive power of the 56 questions of the final PRE tool, Conser et al (2015) detected that only 11 of them showed statistical significance in separating invasive from non-invasive species. Four were the result of merging two similar questions, where both were significant or near significant (e.g., different methods of vegetative reproduction, various biotic and abiotic propagule dispersal mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…Four were the result of merging two similar questions, where both were significant or near significant (e.g., different methods of vegetative reproduction, various biotic and abiotic propagule dispersal mechanisms). Similarly to Conser et al (2015), we evaluated the predictive power of the 38 questions of the USAqWRA scheme for each region and for each species, demonstrating that 8 of them are the most powerful in separating invasive from non-invasive species. These questions were classified into groups because was the result of merging similar questions: (1) Ecology and habitat of the species (questions 2, 4, 6); (2) seeding ability (question 20) and (3) potential of impact and damage to natural areas (questions 24-26, 29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective screening tools have long been sought to assess the potential invasiveness (i.e., potential for spread and/or impact) of exotic species (e.g., the Australian Weed Risk Assessment; Pheloung et al 1999, He et al 2018; and the Environmental and Socio-economic Impact Classification of Alien Taxa (EICAT/SEICAT) tools; Blackburn et al 2014, Bacher et al 2018. Most existing screening tools, however, are based primarily on a priori assumed importance of individual traits and naturalization history beyond native ranges (Gordon et al 2008, Koop et al 2012, Conser et al 2015.…”
Section: Introductionmentioning
confidence: 99%